Effects of Cichorium intybus on serum oxidative stress, liver and kidney volume, and cyclin B1 and Bcl-2 levels in the brains of rats with ethanol induced damage - Ergul Erkec, Ozlem; Arihan, Okan; Colcimen, Nese; Kara, Mehmet; Karatas, Ersin; Demir, Halit; Cetin Ragbetli, Murat (Cellular and Molecular Biology, 2018)
We investigated the effects of an aqueous root extract of Cichorium intybus on Bcl-2 and cyclin B1 levels in the brain, kidney and liver volumes and changes of serum total antioxidant status (TAS) and total oxidant status (TOS) levels in ethanol induced damage in rats. The rats were divided into five groups: non-treated controls (C), maltodextrin in tap water treated (MD), 6.4% ethanol in tap water treated (ET), Cichorium intybus + maltodextrin in tap water treated (CI+MD), and Cichorium intybus + 6.4% ethanol in tap water treated (CI+ET). Rats in the CI+MD and CI+ET groups were treated with 200 mg/kg water extract of Cichorium intybus. Chronic ethanol aMDinistration significantly increased cyclin B1 and decreased Bcl-2 levels in the brain and significantly decreased TAS values, increased TOS values of serum and significantly decreased kidney volume in the ET group. There was no significant difference in the liver volume or liver cell count. Our data revealed that ethanol aMDinistration induces an overexpression of cyclin B1 and decreases levels of Bcl-2 in rat brains and induced oxidative stress in the blood. C. intybus treatment possessed a partial amelioration effect on cyclin B1 levels and TAS values.